On the Stability of Fast Polynomial Arithmetic - Köhler, Sven; Ziegler, Martin (Proc. 8th Conference on Real Numbers and Computers)
Operations on univariate dense polynomials—multiplication, division with remainder, multipoint evaluation—constitute central primitives entering as build-up blocks into many higher applications and algorithms. Fast Fourier Transform permits to accelerate them from naive quadratic to running time O(n·polylogn), that is softly linear in the degree n of the input. This is routinely employed in complexity theoretic considerations and, over integers and finite fields, in practical number theoretic calculations. The present work explores the benefit of fast polynomial arithmetic over the field of real numbers where the precision of approximation becomes crucial. To this end, we study the computability of the above operations in the sense of Recursive Analysis as an effective refinement of continuity. This theo- retical worst-case stability analysis is then complemented by an empirical evaluation: We use GMP and the iRRAM to find the precision required for the intermediate calculations in order to achieve a desired output accuracy.

Physically-Relativized Church-Turing Hypotheses - Ziegler, Martin (Applied Mathematics and Computation)
We turn the physical Church-Turing Hypothesis from an ambiguous source of sensational speculations into a (collection of) sound and well-defined scientific problem(s): Examining recent controversies and causes for misunderstanding concerning the state of the Church- Turing Hypothesis (CTH), it is suggested to study the CTH ‘sharpened’ relative to an arbitrary but specific physical theory—rather than vaguely referring to “nature” in general. For this purpose we combine physical structuralism with computational complexity theory. The benefits of this approach are illustrated by some exemplary results on computability and complexity in computational physics.

A Meta-Theory of Physics and Computation - Ziegler, Martin (Verhandlungen der Deutschen Physikalischen Gesellschaft)

An explicit solution to Post's Problem over the reals - Meer, Klaus; Ziegler, Martin (Journal of Complexity)

Entscheidungsprobleme im Supply Chain Management - Quantitative Lösungsansätze für den Mittelstand

Lehr-Lernforschung und Grundschulpädagogik

Vorschulische Bildungsprozesse in Mathematik und Naturwissenschaften

Bedingungen für erfolgreiche Leselernprozesse bei leistungsschwächeren Kindern - Hellmich, Frank (Chancenungleichheit in der Grundschule – Ursachen und Wege aus der Krise)

Chancengleichheit im mathematischen Anfangsunterricht durch eine frühzeitige Diagnose mathematischer Vorläuferfähigkeiten - Hellmich, Frank; Sämisch, Markus (Chancenungleichheit in der Grundschule – Ursachen und Wege aus der Krise)

Erklärungsfaktoren für Geschlechterunterschiede in der Lesekompetenz bei Grundschulkindern am Ende ihrer Grundschulzeit - Hellmich, Frank (Zeitschrift für Grundschulforschung. Bildung im Elementar- und Primarbereich)

Empirische Bildungsforschung und Grundschulpädagogik - Hellmich, Frank (Lehr-Lernforschung und Grundschulpädagogik)

Selbstbezogene Kognitionen und Interessen von Mädchen und Jungen im Mathematikunterricht der Grundschule - Hellmich, Frank; Jahnke-Klein , Sylvia (Kinder und ihr Geschlecht. Jahrbuch Frauen- und Geschlechterforschung in der Erziehungswissenschaft)

Individuelle und schulische Bedingungen im Leseunterricht der Grundschule - Hellmich, Frank (Checkpoint Literacy. Tagungsband 1 zum 15. Europäischen Lesekongress 2007 in Berlin)

"Ich mach` das so, wie machst du das eigentlich?" – Diagnose und Förderung von Lernstrategien bei Kindern im Grundschulalter - Hellmich, Frank (Sache - Wort - Zahl)

Diagnose mathematischer Vorläuferfähigkeiten im vorschulischen Bereich - Hellmich, Frank; Jansen, Sven (Vorschulische Bildungsprozesse in Mathematik und Naturwissenschaften)

Förderung mathematischer Vorläuferfähigkeiten im vorschulischen Bereich – Konzepte, empirische Befunde und Forschungsperspektiven - Hellmich, Frank (Vorschulische Bildungsprozesse in Mathematik und Naturwissenschaften)

Association of prepubertal body composition in healthy girls and boys with the timing of early and late pubertal markers - Buyken, Anette; Karaolis-Danckert, Nadina; Remer, Thomas (The American Journal of Clinical Nutrition)

Consumption of sugar-sweetened beverages and its association with nutrient intakes and diet quality in German children and adolescents - Libuda, Lars; Alexy, Ute; Buyken, Anette; Sichert-Hellert, Wolfgang; Stehle, Peter; Kersting, Mathilde (British Journal of Nutrition)

Refinement in the Presence of Unknowns - Wehrheim, Heike (Electr. Notes Theor. Comput. Sci.)

Alloy as a Refactoring Checker? - Estler, H.{-}Christian; Wehrheim, Heike (Electr. Notes Theor. Comput. Sci.)